Responsibilities of Regency/Municipal Governments in Managing Basic Education Affairs - Pattinasarany, Yohanes (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The handover of basic education affairs by the central government to regencies/municipalities, raises the responsibility of district/city local governments to manage basic education affairs in order to provide quality basic education to local community members.Purposes of the Research: Analyze the form of responsibility for the district/city government in managing basic education affairs.Methods of the Research: The writing method used is normative law, by reviewing positive legal provisions, legal principles, legal principles and legal doctrines in order to build legal arguments related to the substance under study.Results of the Research: The results of the study show that the form of responsibility of the district/city government in managing government affairs in the field of basic education involves administration, institutions, finance, and facilities and infrastructure, and so on through government policies and legal actions as well as government services in the field of basic education to fulfill the rights of every citizen. citizens to obtain quality basic education services as a basis for continuing to secondary education and higher education. Neglect of the implementation of the said responsibility can be held legally responsible through accountability.